Chemical health threats : assessing and alerting - Duarte-Davidson, Raquel; Gaulton, Tom; Wyke, Stacey; Collins, Samuel (Issues in toxicology., 2019)
This book examines the European guidelines for the risk assessment and management of serious international public health threats.